Case Report: An Unusual Case of Ectopic ACTH Syndrome Caused by Mediastinal Paraganglioma - Li, Bo; Yan, Zhe; Huang, Hui (Frontiers in Endocrinology, 2022)
Ectopic adrenocorticotrophic hormone (ACTH) syndrome is not common, which caused by paraganglioma is quite unusual. We herein present a 40-year-old Chinese male whom was diagnosed with ACTH-dependent Cushing’s syndrome. However, the localization of ACTH source was troublesome due to the inconsistent results of high dose dexamethasone suppression test (HDDST) and desmopressin (DDAVP) stimulation test. The bilateral inferior petrosal sinus sampling (BIPSS) was performed, and ectopic ACTH syndrome was diagnosed. After 68Ga-DOTATATE-PET/CT and 18F-FDG-PET/CT finished, it was localized in anterior mediastinum. Post-operation histopathology demonstrated an ACTH-secreting mediastinal paraganglioma. The patient obtained a complete clinical remission after mediastinal tumorectomy.